The diversity and abundance of phytoplankton and benthic diatoms in varying environmental conditions in Kok River, Chiang Rai, Thailand as bio-indicators of water quality - TIPPAWAN PRASERTSIN; KRITTAWIT SUK-UENG; KITTIYA PHINYO; EKKACHAI YANA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prasertsin T, Suk-ueng K, Phinyo K, Yana E. 2021. The diversity and abundance of phytoplankton and benthic diatoms in varying environmental conditions in Kok River, Chiang Rai, Thailand as bio-indicators of water quality. Biodiversitas 22: 1853-1862. The study of living organisms was important information for bio-indicators which was utilized to assess the quality of the environment. In the river ecosystem, the algae with which one organism was interesting accordingly considered the relationship of 2 groups algae, including phytoplankton and benthic diatoms and the physical-chemical parameters of Kok River Chiang Rai, Thailand.  Phytoplankton and benthic diatoms were collected from five sampling sites along the Kok River during January (cool dry), March (summer), and June (rainy season) 2018, and assessed as bio-indicators to monitor environmental factors that represent water quality across varying conditions and periods. Fifty-seven species of phytoplankton and thirty-nine species of benthic diatoms were found. The phytoplankton mainly belonged to the phylum Bacillariophyta (diatom group). Physical and chemical factors affecting the dominant phytoplankton and benthic diatom species were subjected to canonical correspondence analysis (CCA). Results showed that planktonic and benthic Gomphonema lagenula positively correlated with ammonium nitrogen, recording highest abundance during the rainy season. Abundance of Achnanthidium straubianum, a planktonic and benthic diatom, and Navicula cincta negatively correlated with river velocity and water conductivity, with lowest numbers during the rainy season. Water trophic status evaluated from the main parameters of the AARL-PC score indicated that during the cool dry and summer seasons all sampling sites were classified as mesotrophic, while during the rainy season they were classified as meso-eutrophic. The combination of phytoplankton and benthic diatom can be used as bio-indicators of water quality in the Kok River and other freshwater ecosystems.